2017
DOI: 10.1021/acs.jafc.6b05386
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Network in Terpenoid Synthesis ofAntrodia cinnamomeain Mycelia and Fruiting Bodies

Abstract: Antodia cinnamomea, a precious brown-rot fungus endemic to Taiwan, has pharmaceutical applications due to its diverse array of metabolites. The terpenoids found in A. cinnamomea contribute to its most important bioactivities. We identified several terpenoid compounds in A. cinnamomea and revealed that their content in mycelium and fruiting body were significantly different. Using next-generation sequencing and an in-house transcriptome database, we identified several terpene synthase (TPS) candidates. After se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…However, three species were amplified as immature cDNA whose open reading frames were shifted and six species were not expressed under the experimental conditions used. Although further investigation is required, gene expression/splicing of certain PpSTSs might be tightly regulated such that some terpene synthases are specifically expressed in the fruiting body (Lin et al ., ) and alternative splicing of fungal genes are possible (Nazir et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, three species were amplified as immature cDNA whose open reading frames were shifted and six species were not expressed under the experimental conditions used. Although further investigation is required, gene expression/splicing of certain PpSTSs might be tightly regulated such that some terpene synthases are specifically expressed in the fruiting body (Lin et al ., ) and alternative splicing of fungal genes are possible (Nazir et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, three species were amplified as immature cDNA whose open reading frames were shifted and six species were not expressed under the experimental conditions used. Although further investigation is required, gene expression/splicing of certain PpSTSs might be tightly regulated such that some terpene synthases are specifically expressed in the fruiting body (Lin et al, 2017) and alternative splicing of fungal genes are possible (Nazir et al, 2010). Sesquiterpene synthases have well-known conserved signature motif sequences that is aspartate-rich and the NSE/DTE motifs, which play vital roles in coordinating Mg 2+ to facilitate ionization of FPP/NPP in the active site (Aaron and Christianson, 2010).…”
Section: Molecular Diversity Of Ppstssmentioning
confidence: 99%
“…Therefore, this is the first report of any enzyme system involved in secondary metabolite biosynthesis from this organism. Only a few reports describe the successful functional characterization of TPSs from the phylum of Basidiomycota [ 35 , 37 , 39 , 42 ]. In this study, the heterologous expression of Copu2 and Copu3 functionally confirmed their identities as sesquiterpene synthases (STPSs).…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al, have found various terpenoid compounds in both liquid cultured mycelium and wild‐type fruiting body of A. cinnamomea (Ling et al, ). Using next‐generation sequencing (NGS) and transcriptome database several terpene synthase (TPS) candidates have been identified.…”
Section: Chemical Componentsmentioning
confidence: 99%
“…Using next‐generation sequencing (NGS) and transcriptome database several terpene synthase (TPS) candidates have been identified. A positive association was found among terpene synthase expression pattern and terpenoid content and it was further identified that several other enzymes are responsible for post‐modification of terpenoids with a genomic DNA scaffold and differential gene expression (Lin et al, ).…”
Section: Chemical Componentsmentioning
confidence: 99%